Cognitive and emotional reactions to pictorial-based risk communication on subclinical atherosclerosis: a qualitative study within the VIPVIZA trial - Elin M. Andersson; Helene Johansson; Steven Nordin; Kristina Lindvall (Taylor & Francis Group, 2023)
AbstractObjectives, setting and subjects Atherosclerosis screening with ultrasound is non-invasive and can be used as part of risk communication. The potential of personalised and pictorial-based risk communication is assessed in VIPVIZA, a population-based randomised controlled trial that aims at optimising cardiovascular disease (CVD) prevention by investigating the impact of visualisation of subclinical atherosclerosis. The present aim was to explore cognitive and emotional reactions evoked by the intervention as well as attitudes to any implemented life style changes in VIPVIZA participants in the intervention group with improved health status and furthermore to study possible interactions between these factors. Understanding mechanisms of action was central since non-adherence to preventive guidelines are often faced in clinical practice.Design In-depth interviews with 14 individuals were analysed with qualitative content analysis.Results Cognitive and emotional processes were highly interlinked and described by the main theme Cognitive and emotional reactions in strong interplay for orchestration of health oriented behavioural change. The informants' descriptions revealed two distinctly different psychological processes which constituted the two subthemes, Problem-focused coping and Encouragement-driven process.Conclusions The results highlight that an interaction between emotional reactions and efficacy beliefs is important in facilitating behavioural change. Furthermore, the results underscore the importance of the risk message being perceived as clear, accurate, reliable and also emotionally engaging and thereby show why atherosclerosis screening and pictorial-based risk communication have the potential to contribute to effective CVD prevention strategies and shared decision making in primary care. Trial registration: ClinicalTrials.gov identifier: NCT01849575, registration 8 May 2013.Key pointsAtherosclerosis screening and pictorial-based risk communication have the potential to contribute to more effective CVD prevention strategies.Risk messages on atherosclerosis status were perceived as clear, accurate, reliable and emotionally engaging.An interplay between efficacy beliefs and emotional reactions facilitated behavioural change.Patients' understanding of CVD risk is important for shared decision-making and of relevance for non-adherence to preventive guidelines.